Force and motion : an illustrated guide to Newton's laws - Zimba, Jason, 1969- (Johns Hopkins University Press, 2009)
Jason Zimba offers a new visual presentation of Newton's three laws of motion, allowing students a new perspective on the conceptual underpinnings of laws that fundamentally explain the workings of the universe.